1999
DOI: 10.2165/00007256-199928040-00006
|View full text |Cite
|
Sign up to set email alerts
|

Medical Issues Relating to the Sydney Olympic Games

Abstract: The Sydney Olympic Games in 2000 represent a significant medical and sporting challenge. Prior planning is the key to optimal performance, and team medical staff should be familiar with major medical and injury concerns of athletes and officials well prior to departure. A comprehensive team medical kit should be organised. Travel will be over great distances for many teams, so particular attention to optimising sleep and hydration is essential. The Olympic village experience can be overwhelming for some athlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…It concerns both performance assessment and athletes' development. Successful debriefing was shown to aid learning, motivation, confidence, psychological and emotional recovery, and self-awareness (Gould et al, 1999;Hogg, 1998Hogg, , 2002Milne et al, 1999). It also enables teams to improve performance, decrease negative emotional effects, and foster coacheathlete relationships (Hogg, 2002;McArdle et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It concerns both performance assessment and athletes' development. Successful debriefing was shown to aid learning, motivation, confidence, psychological and emotional recovery, and self-awareness (Gould et al, 1999;Hogg, 1998Hogg, , 2002Milne et al, 1999). It also enables teams to improve performance, decrease negative emotional effects, and foster coacheathlete relationships (Hogg, 2002;McArdle et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that hockey players are more likely to overeat in a buffet environment due to the abundance of food items not normally available at home (Smart & Bisgoni, 2001). Athletes may also vary from their usual competition intake because they have the opportunity to consume a wide range of food that may be different, both in taste and composition, from their usual intake in their home environment (Milne, Shaw, & Steinweg, 1999;Reilly, Waterhouse, Burke, Alonso, & International Association of Athletics Federations, 2007). Food choice may be influenced by a number of factors including nutrition knowledge, availability, aesthetic properties, nutrient composition, convenience, peer pressure, and cultural acceptability of items (Nestle et al, 1998;Smart & Bisgoni, 2001).…”
mentioning
confidence: 99%
“…A magasabb sérülési ráta a nagyobb kockázatvállalásra, a gyengébb felkészültségre és kondicionális állapotra, valamint a védőfelszerelések ritkább használatára vezethető vissza [18]. Nem tekinthető véletlennek, hogy az olimpiai sportágak közül is a téli sportok [22], azon belül is a hódeszka a legnagyobb sérülési aránnyal járó sportág, megelőzve a sísportágakat [23].…”
Section: A Havas Sportok Baleseteinek Predilekciós Tényezőiunclassified